Dreams and parables of sustainable mobilities - Liu, YF (Berghahn Journals, 2022)
There is a myriad of ideas, often from companies and governments, on what sustainable mobilities should look like and how people should be engaging them. Yet top-down narratives do not always adequately reflect laypeople's mobilities on the ground, and so this article explores the idea of dreams as a way of subverting pre-existing imaginations and redistributing freedoms to move sustainably on one's own terms. Dreams as imaginative forms of inquiry could also expand epistemic frontiers to include voices that have hitherto been under-represented. Where personal dreams contest the status quo, the aim is not about dismissing the productive possibilities from experimental dreams of the technological elite. Instead, this discussion uses the rhetoric of parables as a way to caution against enterprises that expand too quickly without means of care to sustain operations. Thus, this article suggests the labors of repair and maintenance as future avenues of research for sustainable mobility.